Electrode and battery
Patent Information
- Application Number
- JP2023140653
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0009】 上述の態様によれば、内部抵抗小さい電池が得られ、歩留まりよく電極を生産できる。
Smart Images

Figure 2025034337000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode and a battery. [Background technology]
[0002] In an electrode used in a lithium ion secondary battery or the like, an active material layer is formed on a current collector. Methods for forming an active material layer on a current collector can be broadly divided into wet methods and dry methods. In the wet method, a slurry containing an active material, a binder, a solvent, etc. is applied to a current collector and dried to produce an electrode. In the dry method, for example, a granule containing an active material is formed in advance and then pressed onto a current collector to form an electrode. In the dry method, an active material layer can be formed on a current collector without going through a process of applying a slurry, so a process of drying the slurry is not required. This results in high production efficiency of electrodes.
[0003] As a method for producing an electrode using a dry method, Patent Document 1 describes a method in which a binder coating liquid is pattern-coated on the surface of a current collector to regularly form binder-coated and binder-uncoated parts, and a powder of a mixture particle containing an active material and a binder is supplied on top of these to form a mixture layer on the current collector. According to this method, the current collector and the active material are bound by the binder coated on the surface of the current collector, and the active materials are also bound to each other by the binder contained in the powder of the mixture particle, so that the peel strength of the mixture layer against the current collector can be ensured. If such a binder is provided on the current collector, it is thought that the mixture layer is easily adhered to the current collector when producing an electrode, the active material layer can be formed quickly, and the yield can be improved. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-78497 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in a battery using an electrode in which an active material layer is formed on a current collector by pattern coating as described above, the active material layer may not adhere sufficiently to the current collector in the non-coated portion of the binder. If the active material layer does not adhere sufficiently to the current collector, the internal resistance of the battery is likely to increase.
[0006] Therefore, an object of the present invention is to provide an electrode that can provide a battery with low internal resistance and can be produced with good yield, and a battery including such an electrode. [Means for solving the problem]
[0007] One aspect of the present invention is an electrode. The electrode is A current collector; a conductive layer including a conductive agent and formed on at least one surface of the current collector; an adhesive layer including a binder and formed on the conductive layer in a predetermined pattern so as to cover a portion of the conductive layer; an electrode active material layer including an electrode active material and formed on a portion of the conductive layer not covered by the adhesive layer and on the adhesive layer; The conductive layer further comprises a binder in an amount of 90% by mass or less of the conductive layer.
[0008] Another aspect of the present invention is a battery including the electrode. Effect of the Invention
[0009] According to the above-mentioned embodiment, a battery having a small internal resistance can be obtained, and electrodes can be produced with a high yield. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a diagram illustrating a laminated structure of an electrode. [Diagram 2] FIG. 4 is a plan view showing an example of a pattern shape of an adhesive layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described.
[0012] (electrode) FIG. 1 is a diagram showing a schematic diagram of a laminated structure of an electrode 1 according to an embodiment. The electrode 1 comprises a current collector 3, a conductive layer 5, an adhesive layer 7, and an electrode active material layer 9.
[0013] The current collector 3 has two surfaces facing opposite directions. The shape of the current collector 3 is not particularly limited and may be a foil, a flat plate, a mesh, or the like. The thickness of the current collector 3 is, for example, 0.001 mm or more and 0.5 mm or less.
[0014] The material of the current collector 3 is not particularly limited, but when the current collector 3 is used for the negative electrode of a battery, the material is preferably selected from copper, stainless steel, nickel, titanium, and alloys containing two or more of these, and is particularly preferably copper. When the current collector 3 is used for the positive electrode of a battery, the material of the current collector 3 is preferably aluminum.
[0015] The conductive layer 5 is a layer containing a conductive agent and formed on at least one surface of the current collector 3. For easy understanding, FIG. 1 shows the conductive layer 5, adhesive layer 7, and electrode active material layer 9 formed only on one surface of the current collector 3, but the conductive layer 5, adhesive layer 7, and electrode active material layer 9 may be formed on both surfaces of the current collector 3. According to the study by the present inventor, when the conductive layer 5 is provided on the surface of the current collector 3, the electrode active material layer 9 adheres well to the current collector 3 through the part of the conductive layer 5 that is not covered by the adhesive layer 7, and the electrode active material layer 9 is less likely to peel off from the current collector 3 than when the electrode active material layer is formed directly on the current collector. In a battery using such an electrode 1, the conductivity at the interface between the electrode active material layer 9, the conductive layer 5, and the current collector 3 is good, and the internal resistance of the battery using the electrode 1 is likely to be small. Furthermore, with such an electrode 1, the electrode active material layer 9 is unlikely to peel off from the current collector 3, and therefore the internal resistance is unlikely to increase even with repeated charging and discharging, resulting in good cycle characteristics.
[0016] It is preferable that the conductive layer 5 is formed (formed by solid coating) over the entire area of the current collector 3 that overlaps with the area in which the electrode active material layer 9 is formed, when viewed from the stacking direction of the conductive layer 5, the adhesive layer 7, and the electrode active material layer 9 (the vertical direction in FIG. 1).
[0017] The conductive agent is not particularly limited as long as it can provide good conductivity, and is a material for reducing the resistance of the electrode. Examples of the conductive agent include carbon black such as acetylene black and ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, carbon nanotubes, carbon nanofibers, carbon nanobrushes, and other carbon fibers.
[0018] The conductive layer 5 contains a binder in addition to the conductive agent, and the binder content is 10% by mass or more of the total mass of the conductive layer 5. As a result of further investigation by the present inventor, it was found that even if the electrode active material layer is to be adhered to the current collector via the conductive layer, if the binder content of the conductive layer is less than 10% by mass, the electrode active material layer 9 does not sufficiently adhere to the current collector 3 via the conductive layer 5. A battery using such an electrode 1 has a large internal resistance. When the binder content of the conductive layer 5 is 10% by mass or more, the electrode active material layer 9 is sufficiently adhered to the current collector 3 via the conductive layer 5, the resistance of the electrode 1 is reduced, and the internal resistance of the battery using the electrode 1 is reduced. In addition, when the electrode active material layer 9 is sufficiently adhered to the current collector 3 via the conductive layer 5, the conductive layer 5 is unlikely to peel off from the current collector 3 when the battery using the electrode 1 is repeatedly charged and discharged, and the cycle characteristics of the battery using the electrode 1 are likely to be improved. The binder content of the conductive layer 5 is preferably 25% by mass or more, and more preferably 35% by mass or more.
[0019] On the other hand, the binder content of the conductive layer 5 is preferably 90 mass % or less of the total mass of the conductive layer 5. When the binder content of the conductive layer 5 is 90 mass % or less, the amount of conductive agent in the conductive layer 5 is ensured, so that the resistance of the electrode 1 is likely to be reduced and the internal resistance of a battery to which the electrode 1 is applied is likely to be small. In addition, the cycle characteristics of a battery to which the electrode 1 is applied are likely to be improved. The binder content of the conductive layer 5 is preferably 80 mass % or less, and more preferably 70 mass % or less.
[0020] Examples of the binder for the conductive layer 5 include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), etc.; conductive polymers such as polyanilines, polythiophenes, polyacetylenes, polypyrroles, etc.; synthetic rubbers such as styrene butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), acrylonitrile butadiene rubber (NBR), etc.; polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, pectin, etc.; and acrylic resins such as acrylate, methacrylate, etc.
[0021] The adhesive layer 7 is a layer containing a binder and formed in a predetermined pattern on the conductive layer 5 so as to cover a part of the conductive layer 5. The adhesive layer 7 has a predetermined pattern shape when viewed from the stacking direction. FIG. 2 shows an example of the pattern shape of the adhesive layer 7. The adhesive layer 7 shown in FIG. 2 has a plurality of dot-shaped regions 7a arranged at intervals in a direction perpendicular to the stacking direction. Therefore, a non-covered region 5a that is not covered by the adhesive layer 7 is formed on the surface of the conductive layer 5. When the adhesive layer 7 is provided, the electrode active material layer 9 is adhered to the conductive layer 5 by the adhesive layer 7 when the electrode 1 is produced, so that even if the electrode active material layer 9 is formed quickly, the electrode active material layer 9 is firmly bonded to the conductive layer 5. Therefore, the electrode 1 can be produced with a high yield. In addition, since the adhesive layer 7 is formed in a predetermined pattern, the electrode active material layer 9 can be well adhered to the current collector 3 by the conductive layer 5 in the non-covered region 5a as described above, and the conductivity at the interface between the electrode active material layer 9, the conductive layer 5, and the current collector 3 is ensured. If the adhesive layer is formed so as to cover the entire surface of the conductive layer 5, the conductivity at the interface will decrease, increasing the resistance of the electrode 1. As a result, the internal resistance of a battery to which the electrode 1 is applied will increase.
[0022] The pattern shape of the adhesive layer 7 may be, for example, a stripe shape, a lattice shape, or the like, in addition to a dot shape. The dot shape may be a fixed shape such as a circle, an ellipse, a polygon (triangle, square, pentagon, hexagon, etc.), or an irregular shape. The arrangement of the dots, the interval between adjacent dots, the interval between the stripes, and the interval between the intersection positions of the lines forming the lattice may be regular or random. The size (maximum length) of the dots is, for example, 50 to 500 μm, and the interval between adjacent dots is, for example, 5 to 100 μm. The interval between the stripes is, for example, 50 to 200 μm. The interval between the intersection positions of the lines forming the lattice is, for example, 50 to 200 μm. These dimensions are determined so that the electrode active material layer 9 and the conductive layer 5 are uniformly bonded along the interface between them.
[0023] The adhesive layer 7 can be produced by, for example, gravure printing. Specifically, the binder liquid, in which a binder is dissolved or dispersed in a solvent, is held in recesses (cells) engraved on the peripheral surface of a gravure roll, transferred to the surface of the conductive layer 5, and dried. The recesses of the gravure roll are formed to have a shape corresponding to the pattern shape of the adhesive layer 7. The concentration of the binder in the binder liquid is determined in consideration of the thickness of the adhesive layer 7 and the accuracy of transfer to the conductive layer 5, and is, for example, 1 to 40 mass %.
[0024] Examples of the binder for the adhesive layer 7 include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), etc.; conductive polymers such as polyanilines, polythiophenes, polyacetylenes, polypyrroles, etc.; synthetic rubbers such as styrene butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), acrylonitrile butadiene rubber (NBR), etc.; polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, pectin, etc.; and acrylic resins such as acrylates, methacrylates, etc.
[0025] The adhesive layer 7 preferably does not contain a conductive agent. The conductive agent is, for example, a conductive agent having the same composition as the conductive agent contained in the conductive layer 5.
[0026] The electrode active material layer 9 is a layer containing an electrode active material, and is a layer formed on the adhesive layer 7 and on the portion of the conductive layer 5 that is not covered by the adhesive layer 7 .
[0027] When the electrode 1 is an electrode used as the negative electrode of a battery, the electrode active material layer 9 is a negative electrode active material layer containing a negative electrode active material as an electrode active material, and when the electrode 1 is an electrode used as the positive electrode of a battery, the electrode active material layer 9 is a positive electrode active material layer containing a positive electrode active material as an electrode active material.
[0028] The negative electrode active material may be a carbon-based active material. As the carbon-based active material, natural graphite, artificial graphite, hard carbon, soft carbon, carbon black, or any mixture thereof may be selected. Natural graphite includes natural graphite with amorphous carbon coated on the particle surface, and similarly, artificial graphite includes artificial graphite with amorphous carbon coated on the particle surface. These natural graphites and artificial graphites may be primary particles, particles in which primary particles are aggregated to form secondary particles, or mixtures thereof. In addition, the negative electrode active material may be a mixture of a carbon-based active material and a silicon-based active material. The negative electrode active material may include a metal material such as aluminum, silver, bismuth, calcium, cerium, indium, magnesium, tin, zinc, or nickel.
[0029] The negative electrode active material layer preferably contains a conductive assistant and a binder in addition to the negative electrode active material.
[0030] The conductive assistant contained in the negative electrode active material layer is a material for reducing the resistance of the electrode. Examples of the conductive assistant include carbon black such as acetylene black and ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, carbon nanotubes, carbon nanofibers, carbon nanobrushes, and other carbon fibers.
[0031] Examples of the binder contained in the negative electrode active material layer include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF), conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles, synthetic rubbers such as styrene butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile butadiene rubber (NBR), and polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, and pectin. In addition, examples of the binder include polyacrylic acid, polymethacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, sodium polymethacrylate, and potassium polymethacrylate; ethyl polyacrylate, butyl polyacrylate, methyl polymethacrylate, ethyl polymethacrylate, butyl polymethacrylate, polyacrylamide, and polyacrylonitrile, and any mixtures thereof. Furthermore, a metal salt of carboxymethylcellulose (for example, sodium carboxymethylcellulose, potassium carboxymethylcellulose) can also be used as a binder. In addition, electrode additives generally used for forming electrodes, such as thickeners, dispersants, and stabilizers, can be appropriately used in the negative electrode active material layer.
[0032] The positive electrode active material is a composite oxide of lithium and a transition metal, such as lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, and lithium-nickel-cobalt-manganese-aluminum composite oxide; TiS 2 , FeS, MoS 2 Transition metal sulfides such as MnO, V 2 O 5 , V 6 O 13 , TiO2 One or more selected from the group consisting of transition metal oxides such as; and olivine-type lithium phosphate oxides. The olivine-type lithium phosphate oxide contains, for example, one or more elements selected from the group consisting of Mn, Cr, Co, Cu, Ni, V, Mo, Ti, Zn, Al, Ga, Mg, B, Nb, and Fe, lithium, phosphorus, and oxygen. These compounds may be those in which some elements are partially substituted with other elements to improve their properties. Among them, as the positive electrode active material, Li with an average particle size of 3 to 15 μm a Ni b Mn c Co d M x O 2 (However, a, b, c, d, and x satisfy 0.9 ≦ a ≦ 1.2, 0 < b < 1, 0 < c ≦ 0.5, 0 < d ≦ 0.5, 0 ≦ x ≦ 0.3, and b + c + d = 1, and M is at least one selected from the group consisting of Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr). It is preferable to use lithium nickel manganese cobalt oxide represented by
[0033] Preferably, the positive electrode active material layer further contains a binder and a conductive assistant in addition to the positive electrode active material.
[0034] Examples of the binder contained in the positive electrode active material layer include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF), conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles, synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR), or polysaccharides such as carboxymethyl cellulose (CMC), xanthan gum, guar gum, and pectin. Examples of the conductive assistant contained in the positive electrode active material layer include carbon black such as acetylene black and ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, carbon nanofibers, carbon nanotubes, carbon nanobrushes, and other carbon fibers. In addition, the positive electrode active material layer may appropriately contain electrode additives that are generally used for forming electrodes, such as thickeners, dispersants, and stabilizers.
[0035] The electrode 1 described above can be produced with good yield, and a battery with low internal resistance can be obtained.
[0036] The coverage of the conductive layer 5, which is the ratio of the area of the conductive layer 5 covered by the adhesive layer 7 to the area of the entire conductive layer 5, is preferably 60% or less. When the coverage of the conductive layer 5 is 60% or less, the resistance of the electrode 1 is likely to be reduced, and the internal resistance of the battery to which the electrode 1 is applied is likely to be small. When the coverage of the conductive layer 5 exceeds 60%, the non-covered region 5a where the electrode active material layer 9 contacts the conductive layer 5 becomes narrow, and the movement of electrons between the conductive layer 5 and the electrode active material layer 9 is locally restricted, which tends to increase the resistance of the electrode 1. In addition, when the coverage of the conductive layer 5 is 60% or less, the cycle characteristics of the battery to which the electrode 1 is applied are likely to be improved. The coverage of the conductive layer 5 is preferably 50% or less, more preferably 45% or less.
[0037] On the other hand, the coverage of the conductive layer 5 is preferably 30% or more. If the coverage of the conductive layer 5 is 30% or more, a larger portion of the electrode active material layer 9 is adhered to the conductive layer 5 when the electrode 1 is produced, thereby improving the yield. The coverage of the conductive layer 5 is preferably 35% or more, and more preferably 40% or more. The coverage of the conductive layer 5 can be adjusted by changing the pattern shape of the adhesive layer 7.
[0038] The coverage of the conductive layer 5 can be calculated by using image analysis software to take an image of the electrode active material layer 9 peeled off from the adhesive layer 7 using a microscope, a scanning electron microscope, or the like. Since the conductive layer 5 is formed on the lower layer side of the adhesive layer 7, the image can be recognized without being affected by the gloss of the current collector 3, and the dot-like regions 7a can be identified on the image.
[0039] The thickness of the adhesive layer 7 is preferably 0.5 μm or less. When the thickness of the adhesive layer 7 is 0.5 μm or less, the resistance of the electrode 1 is easily reduced, and the internal resistance of the battery to which the electrode 1 is applied is easily reduced. When the thickness of the adhesive layer 7 exceeds 0.5 μm, the cycle characteristics of the battery including the electrode 1 may deteriorate. The thickness of the adhesive layer 7 is preferably 0.35 μm or less, more preferably 0.2 μm or less. On the other hand, the thickness of the adhesive layer 7 is preferably 0.01 μm or more. When the thickness of the adhesive layer 7 is less than 0.01 μm, when the electrode active material layer 9 is formed quickly, the electrode active material layer 9 may not be sufficiently bonded to the conductive layer 5 by the adhesive layer 7, and the yield may decrease. The thickness of the adhesive layer 7 is preferably 0.05 μm or more, more preferably 0.1 μm or more. The thickness of the adhesive layer 7 can be adjusted, for example, by adjusting the depth of the recesses provided on the roll peripheral surface of the gravure roll, the viscosity of the binder liquid, and the like.
[0040] The aspect ratio of the conductive agent particles contained in the conductive layer 5 is preferably 10 or less. When the aspect ratio of the conductive agent particles is 10 or less, the resistance of the electrode 1 is easily reduced, and the internal resistance of the battery to which the electrode 1 is applied is easily reduced. In addition, when the aspect ratio of the conductive agent particles is 10 or less, the cycle characteristics of the battery to which the electrode 1 is applied are less likely to deteriorate. The aspect ratio is calculated for a plurality of conductive agent particles, and is obtained as the average value of the ratio (major axis / minor axis) of the major axis to the minor axis when the maximum distance between the parallel lines sandwiching the conductive agent particles is the major axis and the minimum distance is the minor axis. The aspect ratio of the conductive agent particles is preferably 5 or less, and more preferably 3 or less. The aspect ratio of the conductive agent particles is preferably 1.5 or more, and more preferably 2 or more. The shape of the conductive agent particles can be spherical, elliptical, cylindrical, polygonal columnar, scaly, amorphous, etc.
[0041] The thickness of the conductive layer 5 is preferably 3 μm or less. When the conductive layer 5 is thus thin, the energy density of the battery to which the electrode 1 is applied is increased, and the volume of the battery can be reduced. Furthermore, when the conductive layer 5 is thus thin, the rate characteristics of the battery to which the electrode 1 is applied are easily ensured. The thickness of the conductive layer 5 is preferably 1 μm or less, and more preferably 0.5 μm or less.
[0042] On the other hand, the thickness of the conductive layer 5 is preferably 0.04 μm or more. If the thickness of the conductive layer 5 is too thin, the resistance of the electrode 1 is likely to increase, and the internal resistance of the battery to which the electrode 1 is applied is likely to increase. Furthermore, if the thickness of the conductive layer 5 is too thin, the cycle characteristics of the battery to which the electrode 1 is applied are likely to deteriorate. The thickness of the conductive layer 5 is preferably 0.1 μm or more, and more preferably 0.2 μm or more. The thickness of the conductive layer 5 can be adjusted, for example, by adjusting the supply amount and solids concentration of the slurry containing the conductive agent to be attached to the current collector 3.
[0043] The electrode active material layer 9 preferably contains granulated particles formed by solidifying the electrode active material. The granulated particles formed by solidifying the electrode active material are particles in which the electrode active material, the conductive assistant, and the binder are aggregated. Each of the overlapping ellipses of the electrode active material layer 9 shown in FIG. 1 represents a granulated particle. The granulated particles can be used as a material for the electrode active material layer 9 formed by a dry method, so when the electrode active material layer 9 is formed using the granulated particles, a drying step of the slurry, which is required when the electrode active material layer 9 is formed by a wet method, is not required. Here, when the electrode active material layer 9 is formed by a wet method, if the current collector coated with the slurry is transported at high speed in order to increase production efficiency, the transport path required for drying the slurry becomes long, and the equipment for forming the electrode active material layer 9 becomes large. In order to avoid such an increase in size of the equipment, it is necessary to limit the transport speed of the current collector and limit the speed at which the electrode active material layer 9 is formed. However, if the drying step is not required, a conveying path for drying the slurry is also not required, so that the speed at which the electrode active material layer 9 is formed can be avoided without restricting the conveying speed of the current collector. Therefore, if the electrode active material layer 9 is formed using granulated particles, the production efficiency of the electrode 1 can be improved. In this case, if the current collector is conveyed at high speed in order to quickly form the electrode active material layer using the granulated particles, the granulated particles may not adhere well to the current collector, and the bonding strength may be insufficient. In particular, since the electrode active material layer generally contains only the amount of binder required to form the granulated particles, the bonding strength between the granulated particles and the current collector is likely to be insufficient. Since the electrode 1 of this embodiment includes the adhesive layer 7, when the electrode active material layer 9 is formed, the granulated particles are adhered to the conductive layer 5 by the adhesive layer 7, so that when the electrode active material layer 9 is formed quickly, the electrode active material layer 9 is firmly bonded to the conductive layer 5. This allows the electrode 1 to be produced with a good yield using the granulated particles.
[0044] The method for forming the granulated particles is not particularly limited, and examples thereof include spray granulation, stirring granulation, fluidized bed granulation, rolling granulation, extrusion granulation, and compression granulation. These granulation methods may be selected or combined as desired. Examples of the spray granulation method include spray drying granulation. In the spray drying granulation method, for example, a dispersion in which the electrode active material and the conductive assistant are dispersed is sprayed into the high-temperature gas in a spray dryer to form granules. In the stirring granulation method, for example, the electrode active material is mixed and stirred, and the dispersion in which the conductive assistant is dispersed is added to the electrode active material particles while being sprayed, to form granules. The average particle size of the granulated particles is preferably 15 μm or more, more preferably 20 μm or more, and even more preferably 40 μm or more, and is preferably 90 μm or less, more preferably 80 μm or less, and even more preferably 70 μm or less. The average particle size of the granulated particles means the particle size at 50% cumulative value (median size: D50) in the particle size distribution (volume basis) measured by a laser diffraction scattering method.
[0045] The electrode active material layer 9 may not contain granulated particles. The electrode active material layer 9 may be produced by a wet method.
[0046] (battery) The battery of the embodiment includes the electrode 1 of the above embodiment. According to one example, the battery of the embodiment includes a positive electrode, a negative electrode, a separator, an electrolyte, an outer container, a positive electrode terminal, and a negative electrode terminal. At least one of the positive electrode and the negative electrode is the electrode 1 of the above embodiment. In the battery according to the above example, a laminate in which positive electrodes and negative electrodes are alternately laminated with separators interposed therebetween is housed in an outer container together with an electrolyte. A positive electrode terminal electrically connected to a current collector of the positive electrode and a negative electrode terminal electrically connected to a current collector of the negative electrode are each partially or entirely drawn out to the outside of the outer container. One or more positive electrodes, negative electrodes, and separators are provided.
[0047] In the above embodiment, the electrode 1, which is either the positive electrode or the negative electrode, located between both ends in the stacking direction has a conductive layer 5, an adhesive layer 7, and an electrode active material layer 9 formed on both sides of the current collector 3. In the electrodes located at both ends in the stacking direction of the laminate, the conductive layer 5, the adhesive layer 7, and the electrode active material layer 9 are formed only on the surface of the current collector 3 on the side where the separator is located. In addition, when the positive electrode or negative electrode includes an electrode other than the electrode 1 of the above embodiment, the electrode located between both ends in the stacking direction among the electrodes has an electrode active material layer formed on each of both sides of the current collector. The electrodes located at both ends in the stacking direction of the laminate have an electrode active material layer formed only on the surface of the current collector on the side where the separator is located. The current collector of the electrode other than the electrode 1 of the above embodiment is not particularly limited, but is configured in the same manner as the current collector 3 of the electrode 1 of the above embodiment, for example. The electrode active material layer of the electrode other than the electrode 1 of the above embodiment is not particularly limited, but is configured in the same manner as the electrode active material layer 9 of the electrode 1 of the above embodiment, for example.
[0048] The separator may be, for example, a porous separator. The separator may be in the form of, for example, a membrane, a film, or a nonwoven fabric. The porous separator may be, for example, a polyolefin-based porous separator such as a polypropylene-based or polyethylene-based porous separator; a porous separator formed of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, or a polyvinylidene fluoride-hexafluoropropylene copolymer; or the like.
[0049] The laminate may be in the form of a flat plate or a spiral.
[0050] The electrolyte is a non-aqueous electrolyte, and is preferably a mixture containing a chain carbonate such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), di-n-propyl carbonate, di-t-propyl carbonate, di-n-butyl carbonate, di-isobutyl carbonate, or di-t-butyl carbonate, and a cyclic carbonate such as propylene carbonate (PC) or ethylene carbonate (EC). The electrolyte is preferably a mixture of such a carbonate and lithium hexafluorophosphate (LiPF 6 ), lithium borofluoride (LiBF 4 ), lithium perchlorate (LiClO 4 ) or other lithium salts dissolved in it.
[0051] The positive electrode terminal may be made of aluminum or an aluminum alloy, and the negative electrode terminal may be made of copper, a copper alloy, or a nickel-plated copper or copper alloy.
[0052] The outer container may be, for example, a flexible film having a resin layer provided on the front and back sides of a base metal layer such as aluminum, or a can made of a metal such as aluminum, iron, or stainless steel.
[0053] Examples of the shape of the battery include a pouch-type battery housed in an outer container mainly made of an aluminum film, and also includes a square-type, cylindrical-type, coin-type, or button-type battery housed in an outer container using a metal can.
[0054] The battery of this embodiment is suitable as a non-aqueous electrolyte secondary battery, in particular a lithium ion secondary battery. EXAMPLES
[0055] In order to examine the effect of the present invention, test batteries were made using negative electrodes and positive electrodes made with various specifications.
[0056] (Production of negative electrodes) A slurry containing carbon black (manufactured by Imerys) as a conductive agent and polyvinylidene fluoride (PVDF) as a binder was applied to a copper foil serving as a negative electrode current collector, and then dried to form a conductive layer of various specifications shown in Table 1 on the negative electrode current collector, thereby obtaining a negative electrode current collector with a conductive layer. Note that in Comparative Example 2, the formation of the conductive layer was omitted.
[0057] Next, polyacrylic acid (PAA) and styrene butadiene rubber (SBR) were dissolved or dispersed in a solvent as binders to prepare a binder liquid of desired viscosity. The binder liquid was attached to the roll peripheral surface of the gravure roll, and the excess binder liquid was scraped off with a doctor blade to be held in the recesses of the gravure roll, transferred to a negative electrode current collector with a conductive layer, and then dried to form an adhesive layer with various specifications shown in Table 1 on the negative electrode current collector with a conductive layer (negative electrode current collector in Comparative Example 2), thereby obtaining a negative electrode current collector with an adhesive layer. The binder / solvent mass ratio of the binder liquid was 30:70. A recess was provided on the roll peripheral surface of the gravure roll so that a dot-shaped region 7a as shown in FIG. 2 was obtained. In Comparative Example 1, the formation of the adhesive layer was omitted.
[0058] Separately from the formation of the conductive layer and the adhesive layer, granulated particles of the negative electrode active material layer were prepared. As the negative electrode active material particles, a dispersion of a conductive assistant was prepared in which artificial graphite with an average particle size of 12 μm and silicon monoxide with an average particle size of 5 μm, single-wall carbon nanotubes (SWCNT) as a conductive assistant, and polyacrylic acid (PAA) and styrene butadiene rubber (SBR) as a binder were highly dispersed together with a solvent. Next, the dispersion of the negative electrode prepared by the above procedure was sprayed by rotating the atomizer at a predetermined rotation speed in a spray dryer to obtain granulated particles. The mass ratio of artificial graphite / silicon monoxide / SWCNT / PAA / SBR was 92.4:5.0:0.1:2.0:0.5. Artificial graphite from Nippon Graphite Industries Co., Ltd., PAA from Fujifilm Wako Pure Chemical Industries, Ltd., and SWCNT from OCSiAl Corporation can be used.
[0059] Next, the obtained granulated particles were supplied at a constant rate to a negative electrode current collector with an adhesive layer (a negative electrode current collector with a conductive layer in Comparative Example 1) traveling at 5 m / min from the delivery side to the take-up side of an electrode coater, and the amount of granulated particles supplied to the press roll by the squeegee roll was adjusted until the granulated particles were compressed by the press roll, after which the negative electrode current collector with an adhesive layer was passed between the press rolls to form an active material layer thereon, thereby obtaining a negative electrode.
[0060] For each of the examples and comparative examples, a plurality of negative electrodes were produced, and the thickness of the conductive layer, the thickness of the adhesive layer, the coverage of the conductive layer, and the aspect ratio of the conductive agent particles of one arbitrarily selected electrode were determined. The thickness of the conductive layer and the thickness of the adhesive layer were each determined as the average value of the thicknesses at three points selected in an image of the cross section of the negative electrode observed by SEM. The coverage of the conductive layer was calculated as described above after peeling off the active material layer from the negative electrode. In this case, a plurality of observation regions were selected from the image of the adhesive layer taken by a microscope or SEM, and the ratio of the area of the dot-shaped regions 7a included in each observation region was calculated for each observation region, and the average value was taken as the coverage of the conductive layer. When the image of the pattern shape of the adhesive layer 7 in Example 1 was observed, the size (maximum length) of the dot-shaped regions 7a was 200 to 250 μm, and the interval between adjacent dot-shaped regions 7a was 30 to 70 μm. The aspect ratio of the conductive material particles was determined as the average value of the ratio of the major axis to the minor axis (major axis / minor axis) calculated for each of 100 conductive material particles randomly selected from the SEM image.
[0061] (Battery manufacturing) The positive electrode active material is LiNi with an average particle size of 4.5 μm. 0.92 Mn 0.03 Co 0.05 O 2 A slurry containing carbon black as a conductive additive and polyvinylidene fluoride (PVDF) as a binder was applied to an aluminum foil as a positive electrode current collector, and then dried and pressed to form an active material layer on the positive electrode current collector, thereby obtaining a positive electrode.
[0062] A positive electrode and a negative electrode are laminated with a polyolefin-based porous separator interposed therebetween, each A negative electrode terminal electrically connected to the negative electrode and a positive electrode terminal electrically connected to each positive electrode were provided to obtain a laminate. Next, LiPF 2 was dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate (ethylene carbonate:diethyl carbonate=3:7 (volume ratio)) and used as an electrolyte. 6 The electrolyte solution in which the above was dissolved to a concentration of 1.0 mol / L was placed in an outer container made of a flexible film together with the obtained laminate, and the container was sealed with the positive and negative terminals extended to the outside to obtain a secondary battery.
[0063] (Yield) For each of the examples and comparative examples, negative electrode 1m 2 The yield was evaluated as "high" when the total number of defects, such as falling off of granulated particles per test, dents and stripes appearing in the negative electrode active material layer, was 1 or 0, and was evaluated as "low" when the total number of defects was 2 or more. "Dent" refers to a part of the negative electrode active material layer where the granulated particles slide against the conductive layer or current collector when the squeegee roll comes into contact with the granulated particles and gather locally, and "stripes" refers to a part of the negative electrode active material layer where the granulated particles are lost due to contact with the squeegee roll.
[0064] (Resistance ratio) A test battery with a remaining capacity (SOC) of 50% was prepared, and a constant current discharge at 1.0 C was performed for 10 seconds at 25°C, and the voltage at the end of the discharge was measured to determine the direct current resistance (DCR) of the battery. The volume of the battery was measured according to JIS Z 8807 "Method of measuring density and specific gravity of solids - Method of measuring density and specific gravity by weighing in liquid". The measured resistance value was normalized by the resistance value of Example 1 and shown in Table 1 as a resistance ratio. It can be said that the smaller the resistance ratio, the smaller the internal resistance of the battery. When the resistance ratio was less than 1.50, the internal resistance of the battery was evaluated as small, and when it was 1.50 or more, the internal resistance of the battery was evaluated as large. The resistance value of Example 1 was 0.7Ω.
[0065] (Rate of resistance increase) At a temperature of 45°C, the battery was charged at a constant current of 1.0 C up to a voltage of 4.2 V, and then charged at a constant voltage of 4.2 V up to a charge cut-off current of 0.015 C. CC discharge was then performed at a discharge rate of 1.0 C and a discharge cut-off voltage of 2.5 V. This charge / discharge cycle was repeated 300 times. The resistance increase rate (%) is the direct current resistance (DCR) of the battery after 300 cycles divided by the direct current resistance (DCR) of the battery at the first cycle. The smaller the resistance increase rate, the smaller the increase rate of the battery's internal resistance.
[0066] [Table 1]
[0067] As can be seen from a comparison between Example 1 and Comparative Example 1, the electrode provided with the adhesive layer can be produced with a good yield. As can be seen from a comparison between Example 1 and Comparative Example 3, a battery fabricated using an electrode having a conductive layer and a binder content of 10 mass % or more has a low rate of increase in the internal resistance of the battery and good cycle characteristics.
[0068] Although the electrode and battery of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments and experimental examples, and various improvements and modifications may be made without departing from the spirit and scope of the present invention. [Explanation of symbols]
[0069] 1 electrode 3 Current collector 5 Conductive layer 5a Uncovered area 7 Adhesive layer 7a Dotted area 9 Electrode active material layer
Claims
1. A current collector; a conductive layer including a conductive agent and formed on at least one surface of the current collector; an adhesive layer including a binder and formed on the conductive layer in a predetermined pattern so as to cover a portion of the conductive layer; an electrode active material layer including an electrode active material and formed on a portion of the conductive layer not covered by the adhesive layer and on the adhesive layer; The conductive layer further comprises a binder that is 90% or less by weight of the conductive layer.
2. 2. The electrode according to claim 1, wherein a coverage rate of the conductive layer, which is a ratio of an area of the conductive layer covered by the adhesive layer to an area of the conductive layer, is 60% or less.
3. 3. The electrode according to claim 1, wherein the adhesive layer has a thickness of 0.5 μm or less.
4. The electrode according to claim 1 or 2, wherein the conductive agent particles have an aspect ratio of 10 or less.
5. 3. The electrode according to claim 1, wherein the conductive layer has a thickness of 0.04 μm or more.
6. 3. The electrode according to claim 1, wherein the conductive layer has a thickness of 3 μm or less.
7. The electrode according to claim 1 , wherein the electrode active material layer contains granulated particles formed by solidifying the electrode active material.
8. A battery comprising the electrode according to claim 1 or 2.
Citation Information
Patent Citations
Method for manufacturing lithium ion secondary battery
JP2014078497A
Cited By
Positive electrode and secondary battery
JP2025171398A